Efficient Heterogeneous Palladium-Catalyzed Transfer Hydrogenolysis of Benzylic Alcohols by Formic Acid - Afewerki, Samson; Palo-Nieto, Carlos; Córdova, Armando (Synthesis, 2020)
An efficient heterogeneous palladium-catalyzed transfer hydrogenolysis of primary, secondary, and tertiary benzylic alcohols using formic acid as hydrogen source has been developed. The resulting hydrocarbon products were obtained in excellent yields. Moreover, the system exhibits high chemoselectivity, reacting only with the hydroxy groups in the presence of other functional groups, and excellent recyclability.
Keywords: benzylic alcohols; heterogeneous catalysis; catalytic transfer hydrogenolysis; formic acid